Explosion suppression experiment of oil storage containers based on porous explosion suppression materials - Xinsheng JIANG; Lei ZHOU; Yunxiong CAI; Dongliang ZHOU; Ri CHEN; Xizhuo QIN (You-qi chuyun)
In order to obtain the most suitable porous explosion suppression material for oil storage containers, the gasoline-air mixture explosion suppression experiment in a closed container was carried out with the three representative explosion suppression materials, such as mesh aluminum alloy, spherical non-metallic material and reticulated polyurethane foam. On this basis, the explosion suppression mechanism was studied, the explosion suppression evolution process was analyzed, and the characteristic parameters of explosion were compared. The results show that the "cold wall effect", "wall effect" and explosion wave suppression theory all play an important role in the suppression of gasoline-air mixture explosion, but various explosion suppression mechanisms have different contributions to the cases with different materials used. When the mesh aluminum alloy and spherical non-metallic material are used to suppress the explosion, the overpressure in the container is inhibited, but the flame develops rapidly due to the disturbance effect, causing the explosion generated rapidly. When the reticulated polyurethane foam is used, the flame and overpressure are well controlled. Herein, the maximum overpressure peak value and explosive power index were taken as the evaluation indexes, and the reticulated polyurethane foam has much better explosive suppression performance than the other two materials. It is indicated that the reticulated polyurethane foam has important engineering application value in the safety monitoring and control of oil and gas.